From Masjidul Haram to Bukittinggi? Islamic reform in West Sumatra - Zakariya, Hafiz (2016)
Islamic reform in Minangkabau region predated 1803 with the return of three famous hajis from Makakh. Indeed, it started with the three hajis' own teacher, Tuanku Nan Tua at Kota Tua Empat Angkat, Bukittinggi.